2004
DOI: 10.1074/jbc.m405562200
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Calbindin-D28k in Calcium Homeostasis Revealed by Mice Lacking Both Vitamin D Receptor and Calbindin-D28k

Abstract: Calbindin (CaBP)-D28k and CaBP-D9k are cytosolic vitamin D-dependent calcium-binding proteins long thought to play an important role in transepithelial calcium transport. However, recent genetic studies suggest that CaBP-D28k is not essential for calcium metabolism. Genetic ablation of this gene in mice leads to no calcemic abnormalities. Genetic inactivation of the vitamin D receptor (VDR) gene leads to hypocalcemia, secondary hyperparathyroidism, rickets, and osteomalacia, accompanied by 90% reduction in ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 37 publications
3
57
2
1
Order By: Relevance
“…In addition, we found that vitamin D receptor (Vdr) was induced during this period. Previous studies have shown that VDR regulates calcium absorption by regulating related genes such as calcium transporter 1 and calbindin-D9K in the small intestine (38)(39)(40). Our present results support the notion proposed in a previous study using Vdr null mice (41) that vitamin D is important for development after weaning.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we found that vitamin D receptor (Vdr) was induced during this period. Previous studies have shown that VDR regulates calcium absorption by regulating related genes such as calcium transporter 1 and calbindin-D9K in the small intestine (38)(39)(40). Our present results support the notion proposed in a previous study using Vdr null mice (41) that vitamin D is important for development after weaning.…”
Section: Discussionsupporting
confidence: 92%
“…The same holds true for CR-immunoreactive or CB-D28k-immunoreactive neurons in the respective knockout strains, CBD28k 2/2 and CR 2/2 (Airaksinen et al 1997;Schiffmann et al 1999). The most notable exception is the up-regulation of CB-D9k in epithelial kidney cells in CB-D28k 2/2 mice (Zheng et al 2004). Two plausible explanations for the absence of compensation/homeostatic mechanisms at the level of other Ca 2þ buffers are presented: (I) Neurons once committed to express a certain Ca 2þ buffer have permanently inactivated/repressed the promoter for other Ca 2þ buffers; (II) The specific properties (affinities, kinetics, cooperativity, mobility) of any other Ca 2þ buffer would not be adequate to restore "normal" Ca 2þ signaling (Schwaller 2009 Purkinje cells are characterized by extensive Ca 2þ signaling and high expression levels of PV and CB-D28k and, thus, are well-suited to address these questions.…”
Section: The Ca 2þ Homeostasomementioning
confidence: 64%
“…Renal calbindin-D28k appears to enhance tubular Ca 2+ reabsorption, and a reduction of renal calbindin-D28k is associated with hypercalciuria [28][29][30][31][32]. Findings from a recent in vivo study using a gene-knockout model confirm the critical role of calbindin-D28k in maintaining renal calcium homeostasis [33]. Hypercalciuria is commonly associated with diabetes [4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%